Preparation method for improving water resistance and dyeing stability of noctilucent fiber and application of preparation method
By modifying rare earth luminescent materials through high-temperature consolidation method and coating SiO2, combined with low-temperature carrier dyeing, the problems of luminous fibers in hydrolysis and dyeing processes in humid environments are solved, and water resistance and dyeing stability are improved, and luminescence is maintained. Performance and economic benefits.
Patent Information
- Application Number
- CN202411381766.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Rare earth luminous fibers are easily hydrolyzed in humid environments, resulting in a degradation of luminous performance. The existing dyeing process has the damage to the luminous performance by long dyeing time and high temperatures, which affects the stability and luminous brightness of luminous fibers.
The modified rare earth luminescent material SAOED was prepared by high-temperature consolidation method, and SiO2 coated by sol-gel method, combined with melt spinning method to prepare luminous fibers, and ethyl benzoate was used as the dyeing carrier for low-temperature carrier dyeing.
It improves the water resistance and dyeing stability of the luminous fiber, maintains good luminescence performance, and the dyeing process is green and environmentally friendly, economical, simple and safe.
Smart Images

Figure CN119265737A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of luminous fiber materials, and specifically relates to a preparation method for improving the water resistance and dyeing stability of luminous fiber and an application thereof. Background Art
[0002] Rare earth luminous fiber is a functional and environmentally friendly fiber made of rare earth luminescent materials. It has the characteristics of high added value and sustainable self-luminescence. It is widely used in transportation, aviation and navigation, entertainment clothing and other fields. 2+ ,Dy 3+ SAOED is an inorganic photoluminescent rare earth long afterglow material with the advantages of high fluorescence intensity, long afterglow time, and green environmental protection. It is an excellent raw material for preparing luminous fibers. However, due to the presence of a large number of hydroxyl groups on the surface of SAOED, it is prone to hydrolysis when exposed to humid air or in contact with water for a long time, resulting in a decrease in the afterglow intensity. This makes the stability of the luminous fibers in aqueous solvents poor, and affects whether they can maintain good luminescence functions for a long time during use. SAOED is also prone to agglomeration in organic solvents, and poor organic compatibility brings certain limitations to spinning.
[0003] The current dyeing process generally uses water as a solvent, and it takes a certain dyeing time, which also brings challenges to the dyeing of luminous fibers. At present, a liquid phase deposition method is used to coat an amorphous CaF2 coating layer on the surface of SAOED powder, and it is found that SAOED with a coating amount of 8% has good water resistance and luminescence performance. Secondly, because excessively high temperature will cause thermal annihilation of the luminescent particles inside the luminous fiber, reducing the afterglow performance, under the same dyeing time, high temperature and high pressure dyeing method is more severe than low temperature dyeing to the luminous performance of luminous fiber. Therefore, the use of low temperature dyeing is a key factor in obtaining good luminous performance after dyeing luminous fiber. Therefore, in order to solve the problems of long dyeing time, high temperature damage to the luminescent masterbatch, and contact, reaction, friction, etc. of the luminous fiber in the dyeing environment, which cause the luminous brightness of the luminous fiber to decrease and the luminous time to shorten, it is urgent to develop a luminous fiber with good water resistance, strong stability and good luminous performance and a low-temperature and environmentally friendly dyeing process. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the specification abstract and the invention title of this application to avoid blurring the purpose of this section, the specification abstract and the invention title, and such simplifications or omissions cannot be used to limit the scope of the present invention.
[0005] In view of the above problems and / or the problems existing in the prior art, the present invention is proposed.
[0006] Therefore, the purpose of the present invention is to overcome the deficiencies in the prior art and provide a preparation method and application thereof for improving the water resistance and dyeing stability of luminous fibers.
[0007] In order to solve the above technical problems, the present invention provides the following technical solutions: a preparation method for improving the water resistance and dyeing stability of luminous fiber and its application, characterized in that: comprising:
[0008] The rare earth luminescent material SAOED for luminous fiber is prepared by high temperature consolidation method, and the SAOED is subjected to dehydration condensation reaction with hexadecyltrimethoxysilane to obtain modified SAOED;
[0009] The modified SAOED was inorganically coated with SiO2 by the sol-gel method, and then the luminous fiber was prepared by melt spinning with polyethylene terephthalate as the substrate.
[0010] Ethyl benzoate was selected as dyeing carrier, and the luminous fiber was dyed at low temperature through carrier dyeing method.
[0011] As a preferred embodiment of the preparation method of the present invention, the preparation method of the rare earth luminescent material SAOED for luminous fiber using high temperature consolidation method comprises:
[0012] The raw materials SrCO3, Al2O3, Eu2O3, Dy2O3 and H3BO3 were mixed evenly in a mortar, ultrasonically dispersed for 30 minutes using anhydrous ethanol as a solvent, dried and placed in a tubular high-temperature sintering furnace for full reaction, calcined for 4 hours at 1400°C in a weak reducing atmosphere, and the sample obtained after natural cooling was the rare earth luminescent material SAOED.
[0013] As a preferred embodiment of the preparation method of the present invention, the ratio of the amount of Sr:Al:Eu:Dy in the SrCO3, Al2O3, Eu2O3 and Dy2O3 is 1:2:0.025:0.025; and H3BO3 accounts for 5% of the total.
[0014] As a preferred embodiment of the preparation method of the present invention, the preparation method of the modified SAOED comprises:
[0015] SAOED and HDTMS were mixed, and then added into a mixed solution of anhydrous ethanol and deionized water, and placed in a water bath at 70°C for heating and stirring to fully react. During this period, acetic acid was added dropwise to adjust the pH of the solution. After the reaction, the modified SAOED was washed, filtered, and dried.
[0016] As a preferred embodiment of the preparation method of the present invention, the mass ratio of SAOED to HDTMS is 1:0.8-3, the mass ratio of anhydrous ethanol to deionized water is 1:5, the concentration of acetic acid is 2 mol / L, and the pH is adjusted to be stable at 3.
[0017] As a preferred embodiment of the preparation method of the present invention, the luminous fiber is prepared by dissolving tetraethyl orthosilicate in a mixed solution of ethanol and deionized water, stirring it evenly as a reaction solution and placing it in a 60°C water bath for condensation and reflux reaction for 4 hours, adjusting the pH to 2-3 with dilute sulfuric acid, and continuously heating and stirring to fully hydrolyze it until a uniform and transparent sol is formed;
[0018] Add modified ASOED to the above sol, continue heating and stirring to make the modified ASOED swell and loosen to form a flocculent gel, then place it in a closed environment at room temperature, age and dry for 24 hours, and then place it in a tubular high-temperature sintering furnace for calcination. The sample after deionized water filtration and drying is SiO2 / modified ASOED;
[0019] The PET masterbatch is mixed with SiO2 / modified ASOED, and a spinning aid is added to form a luminous masterbatch through melting, which is extruded by a twin-screw extruder, and then drawn and wound to produce a luminous fiber with good water resistance.
[0020] As a preferred scheme of the preparation method described in the present invention, the mass ratio of TEOS, ethanol and deionized water is 1:10:15, the SiO2 coating amount of modified ASOED is 3%-8%, the calcination temperature is 200°C to 400°C, the calcination time is 4h, and the mass ratio of PET masterbatch to SiO2 / modified ASOED is 8 to 15:1.
[0021] As a preferred embodiment of the preparation method of the present invention, the preparation process of the carrier solution includes dissolving ethyl benzoate and peregal O-25 in deionized water, heating and stirring in a water bath to fully emulsify the ethyl benzoate to obtain a colorless and transparent solution, which is the carrier solution.
[0022] As a preferred embodiment of the preparation method of the present invention, the concentration of ethyl benzoate is 5 g / L, the concentration of peregal O-25 is 0.6 g / L, the water bath temperature is 70° C., and the time is 150 min.
[0023] As a preferred embodiment of the preparation method described in the present invention, the low-temperature dyeing of the luminous fiber by the carrier dyeing method is to weigh the disperse dye and dissolve it in deionized water to make a dye solution, add an appropriate amount of carrier solution to the dye solution, heat it in a water bath, and put the luminous fiber into it after reaching a certain temperature, keep it warm and dye it, and finally wash and dry it; wherein, the concentration of the dye solution is 0.1g / L~0.3g / L, the mass of ethyl benzoate solution in the dye solution is 3g / L~10g / L, the water bath heating temperature is 90°C, and the insulation time is 10~30min.
[0024] Beneficial effects of the present invention:
[0025] The invention modifies the rare earth luminescent material ASOED and then coats it, which not only improves the water resistance and organic compatibility of the ASOED powder, but also plays a good protective role in subsequent applications and enhances its stability; the carrier dyeing method is adopted, and the luminous fiber after low-temperature dyeing still has good luminous performance, and the dyeing process is green and environmentally friendly, with high economic benefits; the process is simple, low-cost and high-safety. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for describing the embodiments. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative labor. Among them:
[0027] Figure 1 These are the undyed and dyed pictures of the luminous fiber prepared in Example 1.
[0028] Figure 2 The luminescence of the luminous fiber prepared in Example 1 in a dark environment is shown in FIG. 1 and FIG. 1 is shown in FIG. 1 . DETAILED DESCRIPTION
[0029] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the embodiments of the specification.
[0030] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein, and those skilled in the art may make similar generalizations without violating the connotation of the present invention. Therefore, the present invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The term "in one embodiment" that appears in different places in this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive with other embodiments.
[0032] Unless otherwise specified, all raw materials used in the examples of the present invention are commercially available, as shown in Table 1 for details.
[0033] Table 1
[0034]
[0035]
[0036] Example 1
[0037] (1) Preparation of modified SAOED: The raw materials SrCO3, Al2O3, Eu2O3, Dy2O3 and H3BO3 were mixed in a mortar according to the ratio of n(Sr)∶n(Al)∶n(Eu)∶n(Dy) of 1∶2∶0.025∶0.025, with H3BO3 accounting for 5% (amount of substance) of the total matrix. The mixture was ultrasonically dispersed for 30 min using anhydrous ethanol as a solvent. After drying, the mixture was placed in a tubular high-temperature sintering furnace for full reaction. The mixture was calcined for 4 h at 1400°C in a weak reducing atmosphere. The sample obtained after natural cooling was the rare earth luminescent material SrAl2O4:Eu 2+ ,Dy 3 + (SAOED). SAOED and HDTMS were mixed at a mass ratio of 1:1.6, and then added to a mixed solution of anhydrous ethanol / deionized water at a mass ratio of 1:5, and placed in a 70°C water bath for heating and stirring to fully react. During this period, 2 mol / L acetic acid was added dropwise to adjust the pH of the solution to 3. After the reaction, the modified SAOED was washed, filtered, and dried to obtain;
[0038] (2) Tetraethyl orthosilicate (TEOS) was dissolved in a mixed solution of ethanol and deionized water, and stirred evenly as a reaction solution, wherein the mass ratio of the three was 1:10:15, and then placed in a 60°C water bath for condensation reflux reaction for 4 hours, and the pH was adjusted to 2-3 with dilute sulfuric acid, and continued to heat and stir to fully hydrolyze until a uniform and transparent sol was formed; modified ASOED was added to the sol according to a 5% coating ratio, and continued to heat and stir to make the modified ASOED swell and loosen to form a flocculent gel, and then placed in a closed environment at room temperature, aged and dried for 24 hours, and then placed in a 300°C tubular high-temperature sintering furnace for calcination for 4 hours. The sample after filtration and drying was SiO2 / modified ASOED; PET masterbatch and SiO2 / modified ASOED were mixed in a mass ratio of 10:1, and a spinning aid was added to form a luminous masterbatch through melting, which was extruded by a twin-screw extruder, and then drawn and wound to produce a water-resistant luminous fiber.
[0039] (3) Dissolve 0.5 g of ethyl benzoate and 0.06 g of chlorpyrifos O-25 in 100 mL of deionized water, and heat and stir in a 70°C water bath for 150 min to fully emulsify the ethyl benzoate to obtain a colorless and transparent carrier solution; weigh 0.02 g of disperse dye and dissolve it in 100 mL of deionized water to prepare a dye solution with a concentration of 0.2 g / L, and add 0.5 g of the carrier solution to the dye solution so that the mass of the carrier solution in the dye solution is 5 g / L, heat in a water bath, and when it reaches 90°C, add the luminous fiber, keep it warm and dye it for 15 min, and finally wash and dry it.
[0040] Example 2
[0041] The difference from Example 1 is that in step (1), the mass ratio of SAOED to HDTMS is 1:0.8.
[0042] Example 3
[0043] The difference from Example 1 is that in step (1), the mass ratio of SAOED to HDTMS is 1:3.
[0044] Example 4
[0045] The difference from Example 1 is that in step (2), modified ASOED is added to the sol at a coating ratio of 3%.
[0046] Example 5
[0047] The difference from Example 1 is that in step (2), modified ASOED is added to the sol at a coating ratio of 8%.
[0048] Example 6
[0049] The difference from Example 1 is that the calcination temperature in step (2) is 200°C.
[0050] Example 7
[0051] The difference from Example 1 is that the calcination temperature in step (2) is 400°C.
[0052] Example 8
[0053] The difference from Example 1 is that in step (2), the mass ratio of PET masterbatch to SiO2 / modified ASOED is 8:1.
[0054] Example 9
[0055] The difference from Example 1 is that in step (2), the mass ratio of PET masterbatch to SiO2 / modified ASOED is 15:1.
[0056] Example 10
[0057] The difference from Example 1 is that in step (3), the mass of ethyl benzoate solution in the dye liquor is 3 g / L.
[0058] Embodiment 11
[0059] The difference from Example 1 is that in step (3), the mass of ethyl benzoate solution in the dye liquor is 10 g / L.
[0060] Example 12
[0061] The difference from Example 1 is that the concentration of the dye solution in step (3) is 0.1 g / L.
[0062] Embodiment 13
[0063] The difference from Example 1 is that the concentration of the dye solution in step (3) is 0.3 g / L.
[0064] Embodiment 14
[0065] The difference from Example 1 is that the heat preservation and dyeing time in step (3) is 10 minutes.
[0066] Embodiment 15
[0067] The difference from Example 1 is that the heat preservation and dyeing time in step (3) is 30 minutes.
[0068] Example 16
[0069] The corresponding hydrophobic and water-resistant properties, afterglow properties, and color fastness properties of Examples 1 to 15 were tested, and the water resistance, luminescence, color fastness, etc. of the prepared luminous fibers were observed respectively.
[0070] (1) The method for testing hydrophobic properties is as follows: the static water contact angle of SiO2 / modified ASOED powder is tested using a water contact angle analyzer (WCA). The samples are evenly pressed on a glass slide to make the surface flat, and then placed on the instrument and deionized water is added for measurement. The size of the hydrophilic contact angle formed between the liquid and the solid is measured to determine the wettability of the liquid to the solid.
[0071] (2) The water resistance test method is: put the prepared SiO2 / modified ASOED powder of equal mass into the same amount of deionized water and stir, and measure the pH of the hydrolyzed solution after 20 minutes. Since the pH of the initial solution is 7, the water resistance of the sample can be characterized by the change of the solution pH. The higher the pH, the faster the sample hydrolysis rate and the worse the water resistance.
[0072] (3) The afterglow brightness test method is: use a fluorescent afterglow brightness tester to test the afterglow characteristics of the sample. Before the test, the sample must be placed in the dark for 24 hours. Conditions: use 1000lx to excite for 15 minutes, wait for 10 seconds before starting sampling, and the time is 1200 seconds.
[0073] (4) The color fastness performance test includes: testing the color fastness to soaping and the color fastness to rubbing of the prepared luminous fiber according to the national standards GB / T3921-2008 and GB / T3920-2008 respectively.
[0074] Combining Examples 1 to 3, it can be seen that changing the mass ratio of ASOED to HDTMS will affect the hydrolysis resistance and luminescence properties of SiO2 / modified ASOED powder. This is because HDTMS is hydrolyzed to form silanols during the heating process. The hydroxyl groups on the silanols simultaneously undergo dehydration condensation with a large number of hydroxyl groups on the surface of the ASOED powder, and finally form a low surface energy siloxane, thereby grafting dense organic hydrophobic long chains on the surface to achieve a hydrophobic effect and enhance organic compatibility. When the mass ratio of ASOED to HDTMS is 1:0.8, the afterglow brightness of the luminescent powder drops to 5.087 cd / m 2 The reason is that HDTMS is not enough to completely react the hydroxyl groups on the surface of ASOED, and the unmodified ASOED will still hydrolyze; when the mass ratio of ASOED to HDTMS is 1:3, the contact angle of the luminescent material is 120° and the afterglow brightness is 5.201 cd / m 2 , which is also lower than that in Example 1. It may be that the self-condensation effect of the excess HDTMS hydrolysis product leads to a decrease in the grafting rate on the ASOED surface. In summary, when SAOED and HDTMS in Example 1 are mixed at a mass ratio of 1:1.6, the hydrolysis resistance and luminescence performance are the best.
[0075] Combining Examples 1 to 3 with Examples 4 to 7, it can be seen that changing the experimental conditions for inorganic coating of modified ASOED will affect the coating effect of modified ASOED. When the coating amount of SiO2 is 8%, although the high-temperature oxidation resistance of modified ASOED is improved, its protective effect on luminescent materials is enhanced, and a contact angle of 139° is obtained, the excitation and emission efficiency of the phosphor is reduced, and the luminescence performance is reduced to 5.704 cd / m 2 When the coating amount is too low, the effect of anti-hydrolysis and protection of the internal powder cannot be achieved; similarly, when the calcination temperature is as low as 200°C, the activity of silicon oxide is relatively small, the coating layer formed is relatively loose, and the afterglow brightness of the luminescent powder is 5.367cd / m 2 The temperature is too high, the activity of silicon oxide is relatively large, it is not easy to control the reaction speed, and it is not possible to form a dense and uniform coating on the surface of the powder. The afterglow brightness of the luminescent powder is 4.945cd / m 2 In summary, the experimental conditions of Example 1 are selected to obtain the best experimental effect.
[0076] Table 2 Properties of SiO2 / modified ASOED luminescent powder
[0077]
[0078] Combining Example 1 with Examples 8 to 9, it can be seen that the mixing mass ratio of PET masterbatch and SiO2 / modified ASOED is the key factor in spinning luminous fiber. When the mass ratio of the two reaches 8:1, the afterglow brightness of the luminous fiber after dyeing reaches 1.131 cd / m 2 However, the fluidity of the two deteriorates during the blending process, and the breakage rate is high, which affects the normal spinning process; when the SiO2 / modified ASOED content is low, the good luminous effect cannot be achieved, and the afterglow brightness is 0.998cd / m 2 Therefore, when the mass ratio of PET masterbatch to SiO2 / modified ASOED is 10:1, the best effect is achieved.
[0079] Table 3 Luminous properties of luminous fibers after dyeing
[0080]
[0081] Combining Example 1 with Examples 10 to 15, it can be seen that the amount of carrier, the concentration of the dye solution, and the dyeing time will affect the dyeing and luminescence properties of the luminous fiber. The ideal amount of carrier should be just enough to reach saturation in the dye bath without forming a third phase. Too much carrier will lead to the formation of a third phase and cause more dye to remain in the dye bath, reducing the amount of dyeing. When the carrier solution reaches 10g / L in the dye solution, the soap fastness and sunlight fastness of the luminous fiber are level 3 and 4 respectively, and the afterglow brightness is 1.009cd / m 2 .
[0082] The dye not only occurs on the surface of the luminous fiber, but also enters the interior of the fiber. Therefore, the dye is very likely to cover the luminous masterbatch and affect its luminous performance. When the concentration of the dye reaches 0.3g / L, although the color fastness to soaping and sunlight fastness both reach level 4, the afterglow brightness of the fiber is only 0.898cd / m 2 The length of dyeing time is related to the water resistance of the luminous fiber and the dye uptake rate of the dye. Therefore, choosing the appropriate dye concentration, dyeing temperature and time is the key to the luminous fiber having both excellent luminous performance and good color fastness after dyeing. In summary, the best effect is achieved when the concentration of the ethyl benzoate carrier in Example 1 is 5g / L, the concentration of the dye solution is 0.2g / L, and the heat preservation dyeing time is 15min.
[0083] Comparative Example 1
[0084] The difference from Example 1 is that the ASOED is not inorganically coated, and the afterglow brightness of the final luminescent powder is 4.878 cd / m 2 .
[0085] Comparative Example 2
[0086] The difference from Example 1 is that ASOED is not modified, and the afterglow brightness of the final luminescent powder is 4.774 cd / m 2 .
[0087] Comparative Example 3
[0088] The difference from Example 1 is that the mass ratio of PET masterbatch to SiO2 / modified ASOED is 1:1, and the afterglow brightness of the luminous fiber after final dyeing is 0.467 cd / m 2 .
[0089] Comparative Example 4
[0090] The difference from Example 1 is that the concentration of the dye solution is 1g / L, and the afterglow brightness of the luminous fiber after final dyeing is 0.321cd / m 2 .
[0091] Comparative Example 5
[0092] The difference from Example 1 is that the luminous fiber is dyed without adding ethyl benzoate carrier, and the afterglow brightness of the luminous fiber after dyeing is 0.931 cd / m 2 The color fastness to soap washing and color fastness to sunlight are both level 2.
[0093] In view of the shortcoming that SAOED powder is easy to hydrolyze in water, the present invention first modifies it, dehydrates and condenses the hydroxyl groups on its surface, and forms a low surface energy siloxane, and then coats the modified SAOED with SiO2, so as to achieve the hydrophobic and water-resistant effect of the material. If the powder surface is not modified and only coated with SiO2, the SAOED will be exposed to water or damp during subsequent use due to the rupture of the SiO2 coating layer, resulting in hydrolysis of the powder and reduced luminous performance; if only modified without coating, the powder will have poor high-temperature oxidation resistance during spinning preparation, resulting in poor spinnability and poor dyeing performance, which will limit the subsequent processing and dyeing process of the luminous fiber. In the dyeing process of the luminous fiber, the concentration of the dye and the carrier are the key factors of dyeing. Since the luminescence of the luminous fiber will be blocked by the dye, if the dye concentration is too high, more dye will be dyed on the fiber, which will be more blocked and the luminous performance will be reduced. The addition of carriers can not only increase the dyeing rate, but also achieve low-temperature dyeing, which plays a positive role in the luminous properties of luminous fibers. This is because the small molecules of the carriers can enter the interior of the fibers and combine with the fibers by hydrogen bonds or van der Waals forces, increasing the probability of large holes being generated, allowing the dye to be dyed smoothly. Compared with high-temperature and high-pressure dyeing, low-temperature dyeing not only reduces the damage to the luminescent masterbatch, but also reduces energy consumption and improves economic benefits.
[0094] Table 4 Properties of luminescent powder
[0095]
[0096] Table 5 Properties of luminous fibers after dyeing
[0097]
[0098] Figure 1 The prepared luminous fiber, undyed (left) and dyed (right); Figure 2 The luminescence of the prepared luminous fiber, dyed (left) and undyed (right) in a dark environment.
[0099] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the present invention.
Claims
1. A preparation method for improving the water resistance and dyeing stability of luminous fiber, characterized in that: include, The rare earth luminescent material SAOED for luminous fiber is prepared by high temperature consolidation method, and the SAOED is subjected to dehydration condensation reaction with hexadecyltrimethoxysilane to obtain modified SAOED; The modified SAOED was inorganically coated with SiO2 by the sol-gel method, and then the luminous fiber was prepared by melt spinning with polyethylene terephthalate as the substrate. Ethyl benzoate was selected as dyeing carrier, and the luminous fiber was dyed at low temperature through carrier dyeing method.
2. The preparation method according to claim 1, characterized in that: The method for preparing the rare earth luminescent material SAOED for luminous fiber by high temperature consolidation method comprises: The raw materials SrCO3, Al2O3, Eu2O3, Dy2O3 and H3BO3 were mixed evenly in a mortar, ultrasonically dispersed for 30 minutes using anhydrous ethanol as a solvent, dried and placed in a tubular high-temperature sintering furnace for full reaction, calcined for 4 hours at 1400°C in a weak reducing atmosphere, and the sample obtained after natural cooling was the rare earth luminescent material SAOED.
3. The preparation method according to claim 2, characterized in that: The ratio of the amount of Sr:Al:Eu:Dy in the SrCO3, Al2O3, Eu2O3, and Dy2O3 is 1:2:0.025:0.025; and H3BO3 accounts for 5% of the total.
4. The preparation method according to claim 1, characterized in that: The preparation method of the modified SAOED comprises: SAOED and HDTMS were mixed, and then added into a mixed solution of anhydrous ethanol and deionized water, and placed in a water bath at 70°C for heating and stirring to fully react. During this period, acetic acid was added dropwise to adjust the pH of the solution. After the reaction, the modified SAOED was washed, filtered, and dried.
5. The preparation method according to claim 4, characterized in that: The mass ratio of SAOED to HDTMS is 1:0.8-3, the mass ratio of anhydrous ethanol to deionized water is 1:5, the concentration of acetic acid is 2 mol / L, and the pH is adjusted to be stable at 3.
6. The preparation method according to claim 1, characterized in that: The luminous fiber is prepared by dissolving tetraethyl orthosilicate in a mixed solution of ethanol and deionized water, stirring it evenly as a reaction solution and placing it in a 60°C water bath for condensation and reflux reaction for 4 hours, adjusting the pH to 2-3 with dilute sulfuric acid, and continuously heating and stirring to fully hydrolyze it until a uniform and transparent sol is formed; Add modified ASOED to the above sol, continue heating and stirring to make the modified ASOED swell and loosen to form a flocculent gel, then place it in a closed environment at room temperature, age and dry for 24 hours, and then place it in a tubular high-temperature sintering furnace for calcination. The sample after deionized water filtration and drying is SiO2 / modified ASOED; The PET masterbatch is fully mixed with SiO2 / modified ASOED, and a spinning aid is added to form a luminous masterbatch through melting, which is extruded by a twin-screw extruder, and then drawn and wound to produce a luminous fiber with good water resistance.
7. The preparation method according to claim 6, characterized in that: The mass ratio of TEOS, ethanol and deionized water is 1:10:15, the coating amount of SiO2 on modified ASOED is 3% to 8%, the calcination temperature is 200°C to 400°C, the calcination time is 4h, and the mass ratio of PET masterbatch to SiO2 / modified ASOED is 8 to 15:
1.
8. The preparation method according to claim 1, characterized in that: The preparation process of the carrier solution includes dissolving ethyl benzoate and peregal O-25 in deionized water, heating and stirring in a water bath to fully emulsify the ethyl benzoate to obtain a colorless and transparent solution, which is the carrier solution.
9. The preparation method according to claim 8, characterized in that: The concentration of the ethyl benzoate is 5 g / L, the concentration of peregal O-25 is 0.6 g / L, the water bath temperature is 70° C., and the time is 150 min.
10. The preparation method according to claim 1, characterized in that: The low-temperature dyeing of the luminous fiber by the carrier dyeing method is as follows: weighing a disperse dye and dissolving it in deionized water to prepare a dye solution, adding an appropriate amount of carrier solution to the dye solution, heating it in a water bath, and adding the luminous fiber after reaching a certain temperature, keeping the temperature to dye, and finally washing and drying; wherein, the concentration of the dye solution is 0.1g / L to 0.3g / L, the mass of the ethyl benzoate solution in the dye solution is 3g / L to 10g / L, the water bath heating temperature is 90°C, and the insulation time is 10 to 30min.
Citation Information
Patent Citations
Low-temperature dyeing technology of disperse dye for terylene loose fiber
CN108035170A
Long afterglow luminescent flexible nano cellulose material, preparation method and applications thereof
CN108059953A
Preparation method of spectrum blue shift noctilucent fiber
CN112941660A
Cited By
Color spinning polyester staple fiber noctilucent sewing thread and preparation process
CN120311375A